IMPLEMENTASI SISTEM CERDAS BERBASIS JAVASCRIPT UNTUK E-COMMERCE - Ananda, Kevin (Journal of Information System, Informatics and Computing, 2025)
This article explores the implementation of an intelligent system based on JavaScript in e-commerce platforms to enhance user experience. JavaScript, as a dominant and dynamic programming language in web development, enables the implementation of innovative features such as data-driven product recommendations, interactive chatbots, and efficient shopping cart management. A case study was conducted on the development of an e-commerce prototype using React.js for the user interface, Node.js for server-side management, and MongoDB as the database. This research adopted a quantitative approach, where data were collected from system performance measurements, including response time, recommendation accuracy, and user satisfaction levels. Performance analysis showed that the system provided fast response times and high accuracy, making it an optimal solution for modern e-commerce. This article also discusses the technical challenges faced and potential further developments.